Risky Appearances, Skillful Performances: Female Islamic Preachers and Professional Style in Malaysia. Issue 2 (23rd April 2021) - Kloos, David
ABSTRACT: Mass involvement of women in Islamic associations and public religious expressions has led to an unprecedented demand for women Islamic authorities. Yet, paradoxically, the global Islamic revival has also strengthened conservative norms with regard to the exposure of women's bodies and voices. In Malaysia, women Islamic popular preachers navigate, and to some extent obviate, this tension between publicity and modesty by cultivating a professional style. In the context of mass education, mass mediatization, and a public sphere saturated with techno‐political language, these women combine religious guidance with knowledges and performances more commonly associated with nonreligious professions. They perceive their work and careers as an accumulation of professional skills. They work from offices as well as traditional religious institutions. And they provide specialized, often paid services ranging from conventional religious teaching and preaching to professionalized Islamic healing and media performances. The increasing salience of a professional persona in women's preaching requires an analysis that moves beyond pious exemplarity—a central concern of many anthropological studies of women's religious authority—and that recognizes the central role of professional style and associated performances in the shaping of new Muslim femininities. [ religious authority, professional style, women preachers, Islam, Malaysia ] RESUMEN: La participación masiva de mujeres en asociaciones islámicas y expresiones religiosas públicas ha llevado a una demanda sin precedentes de autoridades islámicas de mujeres. Sin embargo, paradójicamente, el revivalismo islámico global ha fortalecido también normas conservadoras con respecto a la exposición de los cuerpos y las voces de mujeres. En Malasia, mujeres predicadoras populares islámicas navegan, y hasta cierto punto obvian, esta tensión entre publicidad y modestia al cultivar un estilo profesional. En el contexto de la educación masiva, la mediatización masiva, y una esfera pública saturada con lenguaje tecnopolítico, estas mujeres combinan la orientación religiosa con conocimientos y presentaciones más comúnmente asociadas con profesiones no religiosas. Ellas perciben su trabajo y carreras como una acumulación de destrezas profesionales. Trabajan desde oficinas, así como instituciones religiosas tradicionales. Y proveen servicios especializados, a menudo pagados variando desde la enseñanza religiosa convencional y la predicación hasta la sanación islámica profesionalizada y las presentaciones en medios de comunicación. La creciente prominencia de una imagen pública profesional en la predicación de mujeres requiere un análisis que se mueve más allá de la ejemplaridad piadosa –una preocupación central de muchos estudios antropológicos de la autoridad religiosa de las mujeres– y que reconoce el rol central del estilo profesional y las presentaciones asociadas en la formación de las nuevas feminidades musulmanas. [ autoridad religiosa, estilo profesional, mujeres predicadoras, islam, Malasia ]